Implementation Of Snakes And Ladders Game On Cognitive Development Of 5-6 Year Old Children - Asril, Zainal; Zeky, Serpuadi; Utami, Mega; Fitri, Rika (Journal of Islamic Early Childhood Education, 2025)
This research is motivated by the author's observations at Kasih Bunda Salareh Aia Kindergarten, where the snakes and ladders game has been implemented as part of early childhood learning activities. However, there are not many studies that discuss in depth the role of teachers in optimizing the benefits of this game for children's cognitive development. The purpose of this study is to determine the application of the snakes and ladders game in children aged 5–6 years. This study uses a qualitative approach with a descriptive type. Data sources consist of primary data (observation results, interviews, and documentation) and secondary data (documents and photos of activities in the school environment). Data collection techniques were carried out through observation, interviews, and documentation, while data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results show that the snakes and ladders game at Kasih Bunda Salareh Aia Kindergarten is used as a fun, interactive, and educational learning medium, helping children develop cognitive, social-emotional, and motor skills. Children become more understanding of the concepts of numbers, sequences, and strategic thinking, and are able to solve simple problems. Teachers play an important role in integrating games into the learning process, creating a meaningful learning atmosphere, and guiding children to learn while playing enthusiastically.